2011
DOI: 10.2118/122400-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Microvisual Study of the Displacement of Viscous Oil by Polymer Solutions

Abstract: Summary Of the various enhanced-oil-recovery (EOR) polymer formulations, newly developed associative polymers show special promise. We investigate pore and pore-network scales because polymer solutions ultimately flow through the pore space of rock to displace oil. We conduct and monitor optically water/oil and polymer-solution/oil displacements in a 2D etched-silicon micromodel. The micromodel has the geometrical and topological characteristics of sandstone. Conventional hydrolyzed-polyacrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 20 publications
6
51
0
1
Order By: Relevance
“…As a consequence, the criterion for the onset of instability does not depend on the concrete form of the relative permeabilitysaturation function like the Corey exponents, but only on the endpoint values at residual saturations. By now it has been generally accepted that instead of the endpoint mobility ratio the shock-front mobility ratio should be used (Hagoort, 1974; Riaz and Tchelepi Riaz et al, 2007;Buchgraber et al, 2011;Tang and Kovscek, 2011a) as shown in the sketch in Fig. 2 where S shock is the saturation at the shock front.…”
Section: Endpoint Vs Shock-front Mobility Ratiomentioning
confidence: 99%
“…As a consequence, the criterion for the onset of instability does not depend on the concrete form of the relative permeabilitysaturation function like the Corey exponents, but only on the endpoint values at residual saturations. By now it has been generally accepted that instead of the endpoint mobility ratio the shock-front mobility ratio should be used (Hagoort, 1974; Riaz and Tchelepi Riaz et al, 2007;Buchgraber et al, 2011;Tang and Kovscek, 2011a) as shown in the sketch in Fig. 2 where S shock is the saturation at the shock front.…”
Section: Endpoint Vs Shock-front Mobility Ratiomentioning
confidence: 99%
“…In some cases even a minimization of viscosity contrast improves recovery factors. Polymer flooding not only improves recovery on the a pore level (Buchgraber et al 2011;Clemens et al 2013a) but also macroscopically (e.g. Cheng et al 2010) A number of oil fields containing medium viscous oil (in-situ viscosity ranging from 5-50 cP) are located in the Vienna Basin in Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results for heavy oil displaced by water and polymer show that, at zero and low polymer concentrations, relatively long and wide fingers of injectant develop and slowly recover. As polymer concentration increases, many more relatively fine fingers are formed [13]. Wang and Xia compared viscoelastic polymers and pure viscous glycerin solutions having the same viscosity to displace oil, by conducting experiments with glass etched system [14][15][16].…”
Section: Introductionmentioning
confidence: 99%